O Processo de Design Digital: endereçando o desafio da multidisciplinaridade - S. M. Pinheiro, Tânia; Teixeira Monteiro, Ingrid; A. Felipe, Danilo; Libório Sampaio, Andréia (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4215, 2018)
Integrated Project is a type of course offered in the Digital Design program of the Federal University of Ceará, Quixadá Campus. It has the challenge of integrating into a single project some concepts from the areas of Computer Science, Design, Communication and Arts. For the interdisciplinarity to be productive, it was specified PD3 (Digital Disruptive Design Process), a design process based on HCI, Design, and Software Engineering methodologies. In this paper, we present the PD3 applied to the Integrated Project courses, describing how it has been used and evolved, as well as giving lessons learned.